PENGARUH MODEL PBL BERBASIS MEDIA INTERAKTIF BOOK CREATOR TERHADAP HASIL BELAJAR IPAS SISWA SEKOLAH DASAR - Dyah Retno Indarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model based on Book Creator interactive media on students' learning outcomes in Natural and Social Sciences (IPAS) at the elementary school level. This research used a quantitative approach with an experimental method, specifically a pre-experimental design of One Group Pretest–Posttest Design. The sample consisted of 25 fifth-grade students of SD Inpres Minasa Upa selected using a saturated sampling technique. Data were collected through tests, observation, and documentation. The research instrument was a validated pretest and Posttest. Data analysis used descriptive and inferential statistics, including normality test, t-test, and N-Gain calculation. The results showed an improvement in students’ learning outcomes, where the average score increased from 62.40 in the pretest to 86.80 in the Posttest. Learning mastery also increased from 44% to 100%. The N-Gain result was 0.65, categorized as moderate. Furthermore, the t-test result showed that the t-value (9.85) was higher than the t-table (2.064), indicating that the alternative hypothesis was accepted. In conclusion, the Problem Based Learning (PBL) model based on Book Creator interactive media has a positive and significant effect on elementary students’ IPAS learning outcomes